BRIONONIC ACID FROM THE HEXANE EXTRACT OF Sandoricum koetjape MERR STEM BARK (meliaceae) - Tukiran Tukiran; Saidah Saidah; Suyatno Suyatno; Nurul Hidayati; Kuniyoshi Shimizu (Universitas Gadjah Mada, 2006)
An oleane-type triterpenoid, briononic acid was isolated from hexane extract of the stem bark of Sandoricum koetjape Merr. (Meliaceae). This structure had been established based on spectroscopic data (UV, IR, and NMR) and by comparison with spectroscopic data of related compound that had been reported.